The possible truths: the importance of Anthropology to Law - Capela, Gustavo (Revista de Estudos Empíricos em Direito, 2018)
This article discusses de problem of truth as it is presented within the discourse of Law. It contains arguments that point towards a "need for anthropology" in a scientific approach to solving problems under that which some call "the science of the law", or jurisprudence. To illustrate this argument, we utilize empirical data that support the necessity for a more ample and more scientific openess to the diverse within law’s epistemology.